Pelatihan Pemanfaatan Figma sebagai Upaya Peningkatan Kompetensi Desain Digital Guru Informatika SMP di Salatiga - Pratyaksa Ocsa Nugraha Saian; Hanita Yulia (Madani : Indonesian Journal of Civil Society, 2026)
The Informatics subject in the Merdeka curriculum is believed to be the answer to improving modern technology competence. Understanding data structures and workflows and producing digital content using digital media are some of the learning outcomes of Informatics in phase D/SMP (middle school) that need to be taught practically and engagingly. One application that can be used to support this learning is Figma. Based on interviews with Board of the MGMP (Musyawarah Guru Mata Pelajaran) TIK in Salatiga, it was found that they require training in the use of Figma. Therefore, this community service activity was carried out to provide training on using Figma for application prototyping and creating digital content such as presentation materials. The training was conducted offline at SMP Negeri 4 Salatiga (Salatiga Public Middle School 4) and was attended by 26 Informatics teachers from various middle schools in Salatiga. This training activity showed that participants already understood and were confident in using Figma in their future learning processes. This was evident from the final assessment of teachers' understanding level, which reached a score of 74.10%, falling into the "Understand" category. The activity also received positive responses from participants, who plan to utilize Figma to support Informatics learning.